Effect of Ionizing Energy on Extracts of Quillaja Saponaria to Be Used as an Antimicrobial Agent on Irradiated Edible Coating for Fresh Strawberries - Zuniga-Navarro, G; Pizarro-Rojas, M; Contreras-Arredondo, R; Junqueira-Conceicao Goncalve, M (2012)
Incorporating antimicrobial compounds into edible films or coatings provides a novel way to improve the safety and shelf life of ready-to-eat foods. Diverse studies with Quillaja saponaria Mol. (popularly named quillay) extracts have demonstrated their potential as antifungal agents against phytopathogenic fungi. Crosslinking induced by ionizing radiation is an effective method for the improvement of both barrier and mechanical properties of the edible films and coatings based on milk proteins. However there are few reports about the effects of ?-radiation on plant extracts. The aim of this work was to evaluate the effect of ionizing radiation (0, 5, 10, 15, 20, 25 and 35. kGy) on extracts prepared from in vitro plants of Q. saponaria to be used as antimicrobial agent in irradiated edible coating based on calcium caseinate and whey protein isolated, and also to establish the concentration of Q. saponaria extract to be added as an antifungal agent in the coating. Gamma irradiation since 15. kGy affects negatively the antimicrobial activity and metabolites composition of extract of Q. saponaria by reducing compounds of phenolic nature. Otherwise no effect on saponins profile was observed even at higher doses. It was possible to conclude that the antifungal activity of Q. saponaria extract is mainly related to phenolic compounds content. In addition, our work also shows that to obtain an efficient antifungal protection is necessary to add a minimum concentration of 6% of the extract after the coating irradiation. © 2011 Elsevier Ltd.